2023
DOI: 10.1007/s10551-022-05322-8
|View full text |Cite
|
Sign up to set email alerts
|

How Multi-Source Gossip Affects Targets’ Emotions and Strategic Behavioral Responses

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…Naeem et al (2020) [15] suggest that when employees encounter workplace negative gossip, they may feel attacked or unfairly treated, further intensifying negative emotions. Zong et al (2023) [16] found that employees targeted by gossip may attribute the negative discussions about themselves to their own negative behaviors and characteristics. This internal attribution can have a destructive impact on an individual's sense of self-worth and self-esteem, causing employees to feel ashamed.…”
Section: Organizational Levelmentioning
confidence: 99%
“…Naeem et al (2020) [15] suggest that when employees encounter workplace negative gossip, they may feel attacked or unfairly treated, further intensifying negative emotions. Zong et al (2023) [16] found that employees targeted by gossip may attribute the negative discussions about themselves to their own negative behaviors and characteristics. This internal attribution can have a destructive impact on an individual's sense of self-worth and self-esteem, causing employees to feel ashamed.…”
Section: Organizational Levelmentioning
confidence: 99%
“…In response, employees become more likely to gossip (Houmanfar and Johnson, 2004). Empirical research has shown that organizational gossip is associated with anger and shame (Zong et al , 2023), perceived organizational politics, compassion (Khan and Chaudhary, 2023), employees’ mental health and psychological capital (Cheng et al , 2023). Organizational gossip has a negative relationship with organizational identity (Xie et al , 2022) and threat to self-respect and a positive relationship with supervisor civility and psychological distress (Ye et al , 2022).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Previous studies have demonstrated that organizational gossip undermines organizational citizenship (Martinescu et al , 2021), impairs job performance (Xie et al , 2019) and increases emotion exhaustion and indifference (Georganta et al , 2014). In addition, organizational gossip causes a decrease in perceived morality and an increase in sanction behaviors (Kakarika et al , 2023), a decrease in helping behavior, an increase in information disguising behavior (Cheng et al , 2023) and in social undermining (Zong et al , 2023), and ego depletion (Khan et al , 2022).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Most studies used either time-lagged (e.g., [71,103]) or cross-sectional designs (e.g., [69,115]). Experimental study designs that allowed for causal inferences were scarce (e.g., [17,73]). The few longitudinal studies were mostly qualitative field studies (e.g., [26,60]).…”
Section: Review Findingsmentioning
confidence: 99%
“…This focus has underscored workplace gossip as an important organizational behavior. Indeed, workplace gossip has become a popular research topic among scientific scholars and practitioners, with a substantial increase over the past few years in empirical studies (e.g., [14][15][16][17]).…”
Section: Introductionmentioning
confidence: 99%